HR Training and Development Strategy and Its role in Achieving the Competitive Advantage of Business Organizations. - Khaled Mehdi, Eyad; Edan, Ahmad; Kamil Oudah, Bilal (Opción, 2019)
The study aims to adopt a training and development strategy, as an effective strategy in achieving competitive advantage in the Iraqi communications sec- tor. To achieve the objectives of the study, the researcher prepared a question- naire to collect primary information from the study sample, which consisted of (23) items. In light of this, data was collected and analyzed and hypotheses tested using Statistical Package of Social Sciences (SPSS). The sample of the study consisted of 70 managers and heads of departments working in the companies of (ZEN) and (Asiacell). After conducting the descriptive analysis of the study and the regression analysis of the study hypotheses, the study reached a number of results, the most important of which was the statistically significant relationship to the training and development strategy in achieving the competitive advantage. The study recommends the need to pay attention to the training and development strategy due to its significance in the current work environment, which is characterized by competitiveness and change, as well as avoiding the selection of individuals by companies on the basis of fa- voritism or personal characteristics in the training and development process.